The ambiguous boundary between professional and private use of information systems: a bibliometric analysis - Kupfer, Anna; Tiefenbeck, Verena; Staake, Thorsten (European Conference on Information Systems (ECIS 2018), 2018)
Traditionally, Information Systems (IS) research focuses on the use and development of IS within and between organizations. This lens dates back to when IS use was mostly confined to professional contexts. Over the last decades, the application of IS has experienced a strong expansion to private contexts, where a large share of IS investments, increase in computing power, and interaction with IS – in the form of PCs, smartphones, tablets, wearables, etc. – takes place today. Senior scholars have highlighted the need to acknowledge the relevance of private contexts for theory building and to redefine the intellectual core of IS. Therefore, we conducted a bibliometric analysis of the entire set of articles (n=737) published in the top IS outlets for the years 1995, 2005, and 2015. The results suggest that the share of articles focusing on the private context is still small, yet, it has quintupled (from 2 to 10 %) in the past twenty years. Moreover, 11% of the articles analyzed investigate topics that involve both professional and private contexts. The findings contribute to the general discussion on boundaries and trends in IS research and serve as motivation in particular for scholars conducting research on the private use of IS. <br